The messy complexities of democratic engagement and empowerment in participatory design – an illustrative case with a community-based organisation. Issue 1 (2nd January 2020) - Thinyane, Mamello; Bhat, Karthik; Goldkind, Lauri; Cannanure, Vikram Kamath
ABSTRACT: Participatory design has as both its purpose and means, the democratic engagement and empowerment of end-users in design processes. The situation of participatory design, as a unit of analysis, is however, laden with complex power dynamics and interactions amongst participating actants; this contributes to advancing as well as inhibiting both the employment of the means and the achievement of the goals of democratic engagement and empowerment. This paper presents the case of participatory design with a community-based organisation, in the design of technology artefacts for one of their service centres. Using Situational Analysis, a critical qualitative inquiry methodology, the paper unpacks the complex interactions and surfaces the hidden power mechanisms and hegemonic dynamics in the participatory design situation. Further, on the premise that reflection and reflexivity can facilitate critical review, empowerment of users, and self-development in design teams, the paper presents an analysis of the extent to which reflexivity was achieved in the participatory design sessions, and discusses the mechanisms that were employed in this situation to mitigate the identified barriers against democratic engagement and empowerment.